2004
DOI: 10.1111/j.1365-2702.2004.01006.x
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of spirituality: implications for nursing practice

Abstract: It seems that there may be no 'precise' terminology associated with the language used to define spirituality, raising possible implications for nursing practice and nurse education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
148
0
17

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(173 citation statements)
references
References 23 publications
7
148
0
17
Order By: Relevance
“…[4][5][6][7] Though defined in various ways, spiritual care is an essential element in nursing care services as shown by studies conducted in various countries. [8,9] There is a positive association identified between health outcomes and spirituality. [10] Further, the Joint Commission has recognized the importance of spiritual care.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Though defined in various ways, spiritual care is an essential element in nursing care services as shown by studies conducted in various countries. [8,9] There is a positive association identified between health outcomes and spirituality. [10] Further, the Joint Commission has recognized the importance of spiritual care.…”
Section: Introductionmentioning
confidence: 99%
“…Social support requires the existence of social relationships that vary according to structure, strength, type and some conditions, such as reciprocity, accessibility and mutual confidence; social relations provide for inclusion, as well as emotional, material and cognitive resources, among others. As a result of social bonds, individuals can remove themselves somewhat from their problems; giving information is inherent to all support resources; interactions can occur intentionally or unintentionally and can exert a positive or negative influence, which is affected by the acknowledgement of individual needs and how support is perceived; it depends on characteristics of who offers and receives support (14)(15)(16) . For research purposes, one has to select a concept that includes relevant aspects, coherent with the objective to be achieved.…”
Section: Social Support Surveymentioning
confidence: 99%
“…Social support, defined as the level at which interpersonal relationships correspond to certain functions, can be broken down into four classes: appraisal, emotional, informational and instrumental support. Appraisal support refers to expressions and feelings of acknowledgement; emotional support refers to affection, love, empathy, respect; the informational category is related to suggestions, information, advice and opinions; and instrumental support refers to financial help, time dedicated to helping and the availability of resources, goods and services (14) . In addition to family, friends and neighbors, social support can also take the form of organized community involvement.…”
Section: Social Support Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…1 This issue of what is meant by the word spirituality, as opposed to the term religiousness, continues to confound scientific study of this important dimension of human experience. For example, in a qualitative study designed to explore in depth what patients understood by the word spirituality, McSherry et al 2 found that in general most were unclear about its meaning and considered it to be synonymous with religion.…”
mentioning
confidence: 99%